2006
DOI: 10.1897/05-629r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in juvenile coho salmon electro‐olfactogram during and after short‐term exposure to current‐use pesticides

Abstract: For anadromous salmonids, olfaction is a critical sense, enabling return migration. In recent years, several pesticides have been identified that interfere with salmonid olfaction at concentrations in the microg/L range; thus, they may pose a risk to species longevity. In the present study, we investigated the acute effects of five agricultural pesticides on juvenile coho salmon (Oncorhynchus kisutch) olfaction using the electro-olfactogram (EOG), a measure of odorant-evoked field potentials. Electro-olfactogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 36 publications
2
38
1
Order By: Relevance
“…Can we be sure that the lack of a response is not due to the Roundup™ impairing the olfactory epithelium? Tierney et al (2006) showed that it takes approximately 10 min of exposure for 1.0 mg/L of Roundup™ to impair the olfactory system, and an increase in concentration increases the speed of the impairment. In our experiment, we mixed the 5 ml of 0.5 mg/L Roundup™ solution with 5 ml of alarm cue and introduced it to a container with 0.5 L of water giving a final concentration of 0.05 ml a.e./L.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Can we be sure that the lack of a response is not due to the Roundup™ impairing the olfactory epithelium? Tierney et al (2006) showed that it takes approximately 10 min of exposure for 1.0 mg/L of Roundup™ to impair the olfactory system, and an increase in concentration increases the speed of the impairment. In our experiment, we mixed the 5 ml of 0.5 mg/L Roundup™ solution with 5 ml of alarm cue and introduced it to a container with 0.5 L of water giving a final concentration of 0.05 ml a.e./L.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, understanding how prey respond to risk in the presence of Roundup™ and other pesticides deserves further attention. In a study on Coho salmon (Oncorhynchus kisutch), Tierney et al (2006) established that Roundup™ blocks olfaction in fish exposed to 1 mg a.e./L glyphosate acid. There was a significant reduction in electro-olfactogram (EOG) readings 10 min after the exposure started.…”
Section: Introductionmentioning
confidence: 99%
“…For example, rainbow trout were attracted to 6 mg/L of NiCl 2 but avoided 24 mg/L [29]. Alternately, the combination of the four herbicides, two of which are known to evoke olfactory sensory neuron responses (2,4-D and glyphosate; [13]), may have created an interesting odor bouquet. Whether the attraction was a concentration and/or mixture effect, fish chose to expose themselves to herbicide mixtures.…”
Section: Behavioral Responses To and Following Herbicide Exposurementioning
confidence: 99%
“…The omnipresence of AChE across the animal kingdom provides ample opportunity for nontarget species effects. Furthermore, carbamates have previously been shown to alter both EOG responses (Jarrard et al, 2004;Tierney et al, 2006a) and olfactorymediated behaviors in coho salmon (Tierney et al, 2006b). The method in which carbamates impair olfaction remains unknown, as AChE impairment does not obviously translate to impaired olfaction.…”
Section: Introductionmentioning
confidence: 99%